Arabidopsis seed germination responses to osmotic stress involve the chromatin modifier PICKLE - Belin, Christophe (Landes Bioscience, 2008)
pkl mutant seed germination is hypersensitive to ABA treatment due to abnormally high and persistent ABI3 and ABI5 expression. PKL, a putative chromatin modifier, is instrumental to associate ABI3 and ABI5 with silent chromatin in response to ABA. Thus, PKL prevents exaggerated germination arrest responses by shutting off ABI3 and ABI5 expression in response to mild stresses.